Developing Service Quality Strategy for Homestays in Mount Dempo Pagar Alam Regency Using IFAS and EFAS Method - Ardiansyah, Imam; Permata Sari, Mustika; Superwiratni (Unit Bahasa, Politeknik Pariwisata NHI Bandung, 2023)
The purpose of this research is to determine effective strategies for improving the tourism destination in Pagar Alam, South Sumatra through the development of homestays in the Gunung Dempo area. The research method used is a combination of qualitative and quantitative methods. The qualitative method is used to describe the appropriate strategies, while the quantitative method is used to analyze the IFAS and EFAS data in the form of numbers. Data were collected through direct observation, interviews, and the distribution of questionnaires to 95 respondents who had visited homestays in the Gunung Dempo area. The results of the SWOT analysis showed that the homestays in the Gunung Dempo area are in quadrant 1, which means that the internal and external conditions are positive and quite good. In this quadrant, homestays are very advantageous with opportunities (1.55) and strengths (1.77). The appropriate alternative strategy for homestay development is an aggressive strategy that utilizes opportunities to increase strengths. Therefore, it can be concluded that alternative strategies and priority strategies can be applied to the development of homestays in the Gunung Dempo area to improve the tourism destination. Suggestions that can be given from this research are to promote advantages in quality of service, unique architecture, and affordable accommodation prices. In addition, it is recommended to collaborate with local and central governments to increase domestic and foreign tourist visits.